Atmospheric aerosol pollution across China: a spatiotemporal analysis of satellite-based aerosol optical depth during 2000–2016. Issue 7 (3rd July 2019) - Feng, Yao; Chen, Dongmei; Zhang, Xuehong
ABSTRACT: Increasing attention has been paid to the deterioration of air quality in China during the past decade. This study presents the spatiotemporal variations of aerosol concentration across China during 2000–2016 using aerosol optical depth (AOD) from the atmospheric product of Moderate Resolution Imaging Spectroradiometer. Percentile thresholds are applied to define AOD days with different loadings. Temporally, aerosol concentration has increased since 2000 and reached the highest level in 2011; then it has declined from 2011 to 2016. Seasonally, aerosol concentration is the highest in summer and the lowest in winter. Spatially, North China and Sichuan Basin are featured by high aerosol concentration with increasing trends in North China and decreasing trends in Sichuan Basin. North, Southeast and Southwest China have been through increasing days with low AOD loading; however, Northeast China has experienced increasing days with high AOD loading. It is likely that air quality influenced by aerosols has notably improved over North China in spring and summer, over Southwest and Southeast China in autumn, but has degraded over Northeast China in autumn.